2012
DOI: 10.1108/02621711211243854
|View full text |Cite
|
Sign up to set email alerts
|

Are business schools doing their job?

Abstract: PurposeThe purpose of this paper is to further the debate on relevance in business education by sharing one business school's experiences.Design/methodology/approachA qualitative survey was carried out, reviewed by two independent collaborators. Conclusions drawn from interviews with more than 30 CEOs and HR Directors, from across all industries, provide findings on how business leaders think about higher education in business.FindingsThe results highlight their perspective regarding: how academic programs can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
51
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 21 publications
1
51
0
Order By: Relevance
“…Mather et al, 2011;Vu et al, 2011;Muff, 2012;Hardin et al, 2014). According to Bennis and O'Toole (2005) business schools have lost their way, moving towards curricula that are increasingly irrelevant to practitioners.…”
mentioning
confidence: 92%
“…Mather et al, 2011;Vu et al, 2011;Muff, 2012;Hardin et al, 2014). According to Bennis and O'Toole (2005) business schools have lost their way, moving towards curricula that are increasingly irrelevant to practitioners.…”
mentioning
confidence: 92%
“…While student demand patterns and increased competition to attract more students (at home and 6 internationally) will, Lorange (2013) suggests require schools to pay increasing attention to flexible learning. Social factors (such as the rise in retirement age) should increase demand for innovative forms of life-long learning, although this need could also be fulfilled by the emergence of 'corporate schools', consultants and in-house non specialist training (Muff, 2012). Syvertsen (2008) suggests business schools are in a position where the ability to innovate is regarded as a source of developing competitive advantage.…”
Section: Challenges Facing Business Schools In the Uk: Competitive Enmentioning
confidence: 99%
“…The Future: Strategic Choices Given the current competitive environment, Muff (2012) (Lavelle, 2013). …”
Section: Challenges Facing Business Schools In the Uk: Competitive Enmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing costs of MBA programs and growing questions about their effectiveness have become primary impetuses for this concern. Most research examining the effectiveness of MBA programs has examined how the programs can be adapted to provide more value to students and their present/future employers (Muff, 2012). This line of research has identified numerous ways by which the structure and/or content of MBA programs can be adapted to possibly improve effectiveness and/or efficiency.…”
mentioning
confidence: 97%